Project Report on Optical Characterization of Skin - AVIK KESH, DEEPAK D, NIDHIN R and PRANAV P (2011)
INTERNAL GUIDE: KAVITHA R, ML DEPT , MVJCE EXTERNAL GUIDE
Keywords: Optical Characterization of Skin